Analyzing the Role of Digital Marketing Attributes on Students’ Intention to Purchase Halal Products - Utari, Raehsya Aidha; Roring, Merriel Callysta; Hidayah, Nurul; Munawaroh, Asyifa Nur Laely (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
The rapid development of digital technology has driven substantial changes in consumption patterns and marketing strategies, including purchasing decisions related to halal products among university students, who represent the generation most adaptive to technological advancement. Growing awareness of the importance of halal assurance and information transparency positions digital marketing as a crucial instrument in shaping purchase intention. This study aims to analyze the influence of Digital Marketing Exposure (DME), Influencer Trust (IT), Digital Content Quality (DCQ), and electronic Word of Mouth (eWOM) on Halal Product Intention (HPI) among university students. The research employs a quantitative approach with purposive sampling involving 100 student respondents in Purwokerto who are active users of digital media. Data were analyzed using multiple linear regression after passing classical assumption tests to ensure model feasibility. The findings indicate that DME has a significant negative effect on HPI, while DCQ and eWOM have significant positive effects. Meanwhile, IT shows no significant effect on HPI. These results suggest that higher-quality digital content and stronger online recommendations increase students’ intention to purchase halal products, whereas excessive digital marketing exposure may instead reduce purchase interest. This study underscores the need for more selective halal digital marketing strategies that prioritize content quality and strengthen eWOM to enhance purchase intention among young consumers. The implications of this research may serve as a reference for businesses, marketers, and policymakers in designing effective and relevant halal marketing strategies in the digital era.